2001
DOI: 10.1038/35107092
|View full text |Cite
|
Sign up to set email alerts
|

Extensive surface diversity of a commensal microorganism by multiple DNA inversions

Abstract: The dynamic interactions between a host and its intestinal microflora that lead to commensalism are unclear. Bacteria that colonize the intestinal tract do so despite the development of a specific immune response by the host. The mechanisms used by commensal organisms to circumvent this immune response have yet to be established. Here we demonstrate that the human colonic microorganism, Bacteroides fragilis, is able to modulate its surface antigenicity by producing at least eight distinct capsular polysacchari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
245
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 306 publications
(250 citation statements)
references
References 9 publications
4
245
0
1
Order By: Relevance
“…In various pathogens, including bacteria and protozoan parasites, several fundamental mechanisms of DNA change are used during invasion of the host. DNA recombination [148][149][150][151] , gene conversion [152][153][154] and gene hypermutation can lead to the evasion of host detection and to the subsequent clonal selection of the pathogenic variant. For example, in trypanosomes, DNA recombination and gene conversion rapidly modify variant surface glycoproteins and allow evasion of host detection 155,156 .…”
Section: Box 2 Mechanistic Similarities Between Pathogenicity and Promentioning
confidence: 99%
“…In various pathogens, including bacteria and protozoan parasites, several fundamental mechanisms of DNA change are used during invasion of the host. DNA recombination [148][149][150][151] , gene conversion [152][153][154] and gene hypermutation can lead to the evasion of host detection and to the subsequent clonal selection of the pathogenic variant. For example, in trypanosomes, DNA recombination and gene conversion rapidly modify variant surface glycoproteins and allow evasion of host detection 155,156 .…”
Section: Box 2 Mechanistic Similarities Between Pathogenicity and Promentioning
confidence: 99%
“…Recent analyses of the genome sequences revealed DNA inversion regions. These results suggested that the ability of B. fragilis to colonise several host environments, behaving either as a member of the microbiota or a pathogen, might be linked to switching of polysaccharide biosynthesis (Krinos et al 2001).…”
mentioning
confidence: 95%
“…The capsular polysaccharide complex (CPC) is a crucial factor in the virulence potential of the species (Comstock et al 1999, Coyne et al 2000. B. fragilis modulates its surface antigenicity, generating distinct CPC combinations (Krinos et al 2001). High variation in the polysaccharide expression of B. fragilis has already been demonstrated using monoclonal antibodies (Patrick et al 1999).…”
Section: Abstract: Bacteroides Fragilis -Adhesion -Redox Potential -mentioning
confidence: 99%
See 2 more Smart Citations